Blast mitigation effect of the foamed cement-base sacrificial cladding for tunnel structures. (30th September 2015) - Zhao, Huiling; Yu, Haitao; Yuan, Yong; Zhu, Hongbo
Highlights: A foamed cement-based material is proposed as the sacrificial cladding of tunnels. We invent an instrument to test impact mitigation effects of the proposed material. A 3D numerical model is used to validate blast mitigation effect on tunnel lining. The feasibility of the material as the sacrificial cladding of tunnels is verified. Abstract: A foamed cement-base material is proposed as the sacrificial cladding of tunnel lining structures to provide the blast mitigation effect. An experimental investigation on responses of the foamed cement-base material specimen with different ingredient proportions to impulse loads is conducted. Two main ingredients of specimens, i.e. the expandable polystyrene (EPS) particles and cement matrix, contribute to the buffer action significantly. Finite element numerical analysis of the composite concrete tunnel lining is performed to assess the blast mitigation effects attributed by the proposed foamed cement-base sacrificial cladding. Dynamic responses caused by blasting loads are mitigated effectively by the proposed foamed cement-base sacrificial cladding with the optimized thickness.